Controlling plasma distributions as driving forces for ion migration during fs laser writing. (22nd April 2015) - Fernandez, Toney Teddy; Siegel, Jan; Hoyo, Jesus; Sotillo, Belen; Fernandez, Paloma; Solis, Javier
Abstract The properties of structures written inside dielectrics with high repetition rate femtosecond lasers are known to depend strongly on the complex interplay of a large number of writing parameters. Recently, ion migration within the laser-excited volume has been identified as a powerful mechanism for changing the local element distribution and producing efficient optical waveguides. In this work it is shown that the transient plasma distribution induced during laser irradiation is a reliable monitor for predicting the final refractive index distribution of the waveguide caused by ion migration. By performing in situ plasma emission microscopy during the writing process inside a La-phosphate glass it is found that the long axis of the plasma distribution determines the axis of ion migration, being responsible for the local refractive index increase. This observation is also valid when strong positive or negative spherical aberration is induced, greatly deforming the focal volume and inverting the index profile. Even subtle changes in the writing conditions, such as an inversion of the writing direction (quill writing effect), show up in the form of a modified plasma distribution, which manifests as a modified index distribution. Finally, it is shown that the superior control over the waveguide properties employing the slit shaping technique is caused by the more confined plasma distribution produced. The underlying reasons for this unexpected result are discussed in terms of non-linear propagation and heat accumulation.